Perancangan Perancangan In Store Media Sebagai Inovasi Media Promosi Couple Distro - Adita Ayu Kusumasari (Jurnal Desain Komunikasi Visual Asia, 2019)
The development of the fashion business is currently experiencing rapid development. This was marked by profileration of innovative and quality fashion products and a variety of loyal fashion followers. A paradigm shifts towards the function of clothing occurs, clothing function does not only to cover and protect the body, but as a reflection of personality, lifestyle, and social status. This has a broad impact on the fashion industry in Indonesia, especially distros. The word distro stands for various kinds of fashion products. Couple Distro is on of the distro located in Malang City. The TOWS method is used to analyze data that has been collected and will be used as a concept for design. The purpose of this study was to design t-shir hang tags, hang tag accessories, shirt hangers, business cards, sales notes, packagin boxes, stuffler, shopping bags, flyers, flyer dispensers, pins, mini banners, x banners, poster in stores, in store catalog, store assistant uniform, cashier table design, room fittings, window display, interior display, and exterior tabel